Waist Circumference as Measure of Abdominal Fat Compartments - Scott M. Grundy; Ian J. Neeland; Aslan T. Turer; Gloria Lena Vega (Hindawi Limited, 2013)
This study examines intercorrelations among waist circumference (WC), intraperitoneal fat (IPF), and subcutaneous abdominal fat (SAF) in ethnically diverse Dallas Heart Study consisting of 1538 women and 1212 men (50% Black). Correlations between fat depots and triglyceride or HOMA2-IR, biomarkers of metabolic syndrome, are also reported. Total abdominal fat (TAF), ASF, and IPF masses were measured by magnetic resonance imaging. The highest correlations with WC according to ethnicity and gender were noted for TAF (R2=0.81-0.88) with progressively lower correlations with ASF (0.65-0.82) and IPF (0.29-0.85). The percentage of IPF relative to TAF was not significantly correlated with WC. For all WC categories, higher IPF/ASF ratios were associated with higher triglyceride levels. In contrast, differences in ratios had little or no association with HOMA2-IR. However, when all data were pooled, IPF was positively correlated with both triglyceride (r=0.358 (men) and 0.363 (women)) and HOMA2-IR (r=0.480 (men) and 0.517 (women)); after adjustment for ASF, IPF was still correlated with triglyceride (r=0.353 (men) and 0.348 (women)) and HOMA2-IR (r=0.290 (men) and 0.221 (women)). WC measures TAF reliably, but its association with IPF depends on IPF/ASF ratios that vary by gender and ethnicity.